CaMKIIα underlies spontaneous and evoked pain behaviors in Berkeley sickle cell transgenic mice. Issue 12 (December 2016) - He, Ying; Chen, Yan; Tian, Xuebi; Yang, Cheng; Lu, Jian; Xiao, Chun; DeSimone, Joseph; Wilkie, Diana J.; Molokie, Robert E.; Wang, Zaijie Jim
Abstract : Abstract: Pain is one of the most challenging and stressful conditions to patients with sickle cell disease (SCD) and their clinicians. Patients with SCD start experiencing pain as early as 3 months old and continue having it throughout their lives. Although many aspects of the disease are well understood, little progress has been made in understanding and treating pain in SCD. This study aimed to investigate the functional involvement of Ca 2+ /calmodulin-dependent protein kinase II (CaMKIIα) in the persistent and refractory pain associated with SCD. We found that nonevoked ongoing pain as well as evoked hypersensitivity to mechanical and thermal stimuli were present in Berkeley sickle cell transgenic mice (BERK mice), but not nonsickle control littermates. Prominent activation of CaMKIIα was observed in the dorsal root ganglia and spinal cord dorsal horn region of BERK mice. Intrathecal administration of KN93, a selective inhibitor of CaMKII, significantly attenuated mechanical allodynia and heat hyperalgesia in BERK mice. Meanwhile, spinal inhibition of CaMKII elicited conditioned place preference in the BERK mice, indicating the contribution of CaMKII in the ongoing spontaneous pain of SCD. We further targeted CaMKIIα by siRNA knockdown. Both evoked pain and ongoing spontaneous pain were effectively attenuated in BERK mice. These findings elucidated, for the first time, an essential role of CaMKIIα as a cellular mechanism in the development and maintenance of spontaneous and evoked pain in SCD, which can potentially offer new targets for pharmacological intervention of pain in SCD. Abstract : CaMKIIα, located in the superficial laminae of the dorsal horn, was hyperactivated in the spinal cord of Berkeley transgenic mice with sickle cell disease. Ongoing and evoked pain behaviors in Berkeley mice can be attenuated by inhibiting or knocking down spinal CaMKIIα.